An optimised placement of the hard quality sensors for a robust monitoring of the chlorine concentration in drinking water distribution systems. (August 2018) - Łangowski, Rafał; Brdys, Mietek A.
Highlights: Sensor placement in drinking water distribution systems. Designed minimal number of sensors for water quality monitoring purposes. Formulated sensors allocation problem as a multi-objective optimisation task. Modelling of chlorine concentration in drinking water distribution systems. Interval estimation for chlorine concentration monitoring purposes. Abstract: The problem of an optimised placement of the hard quality sensors in drinking water distribution systems under several water demand scenarios for a robust monitoring of the chlorine concentration is formulated in this paper. The optimality is understood as achieving a desired trade off between the sensors and their maintenance costs and the accuracy of estimation of the chlorine concentration. The contribution of this work is a comprehensive approach to optimised sensor placement by addressing a single, bi and multi-objective problem formulations including a comparison of the proposed methods in terms of the number of hard sensors placed and the performance of the monitoring system. During the design of optimised sensors placement algorithms, the interval observer, recently developed by the authors is applied as the soft sensors. Finally, for the purpose of validating the performance of the algorithms, they are applied to the model of a real drinking water distribution system.